PENGARUH MODEL PEMBELAJARAN BERBASIS PROJEK TERHADAP HASIL BELAJAR PEMROGRAMAN WEB DINAMIS KELAS XI REKAYASA PERANGKAT LUNAK DI SMK NEGERI 2 PADANG PANJANG - Reza Andrianis; Muhammad Anwar; Zulwisli Zulwisli (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
The purpose of this research is to know the effect of Project-Based Learning to student’s learning outcomes on Dynamic Web Programming subject of class XI Software Engineering in SMK Negeri 2 Padang Panjang. The Type of this research is quasi experimental design. By using post-test only design, this experiment has explained that average value of experiment class is about 77.72, better that average value of control class about 70.65. Hypothetic testing has shown that t value of 3.73 is bigger that t table of 1.67. It means that H0 is rejected and yielding of result and conclusion how PjBL can improve student’s learning outcomes. However, this research has proven that PjBL is more effective and significant to increase student’s learning outcomes rather than conventional method, especially on Dynamic Web Programming subject. Keyword : Project-Based Learning, Learning Outcomes, Dynamics Web Programming